Touristic experiences the living in the Grandma’s house’ project - Correia, Ricardo (2020)
The goal of this research is focused on the project “Living in the Grandma's House” which aims to contribute to the fight against desertification of rural areas and to create unique touristic experiences in rural areas of the Inland North of Portugal. After an ethnographic study, two villages in Trás-os-Montes region were identified in which "Grandma’s" with interest and aptitude to receive visitors through a prior sale and booking (through the website and application of the developed project), were selected to deliver a unique experience to visitors: listen to stories, legends, while sharing a meal in a private house together with the owner which will strengthen the contact between the visitor and the reality visited. It is considered that the effective value of this research is based on the modelling of a feasible and entrepreneurial concept, which is grounded on the particularities of a low-density territory, whose subsequent replication will result in very positive results for the local communities. The methodology adopted is founded on a qualitative approach, which begins with a bibliographical review about the concept of touristic experiences and is based on the analysis of the project “Living in the Grandma's House”.